Третий должен уйти - Колычев Владимир Григорьевич (Лучшая криминальная драма, 2016)
Экземпляры: (20190304) / Инвентарный номер: 34872 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44